Acceleration-based running intensities of professional rugby league match play - Delaney, J. A.; Duthie, G. M.; Thornton, H. R.; Scott, T. J.; Gay, D.; Dascombe, B. J. (International Journal of Sports Physiology and Performance, 2016)
Rugby league involves frequent periods of high-intensity running including acceleration and deceleration efforts, often occurring at low speeds.